Detection of Peste des petits Ruminants Infection in Goats in Assam by Reverse Transcription Polymerase Chain Reaction (RT-PCR) - Malik, Mahmuda; Rahman, Taibur; Sharma, Krishna; Sen, Arnab; Bhattacharjee, Uttaran; Kakoty, Kaushik (International Journal of Livestock Research, 2018)
The present investigation was undertaken to diagnose (PPR) Peste des petits ruminants, a viral disease belonging to Genus Morbillivirus and family Paramyxoviridae by molecular technique i.e., RT-PCR. These will help clinician, pathologist and scientists for better control and prevention of the disease. The tissue materials like lung, spleen, lymph node and intestine were collected in sterile containers during post mortem examination and preserved at -20°C. The samples were further processed for RNA isolation by both TRIsol method and by using commercially available RNA isolation kit. Out of 16 samples collected from natural cases, 9 samples were diagnosed positive by RT-PCR. Among the positive samples N-gene was amplified producing 365 bp amplicon size and H-gene was amplified in eight cases producing 347 bp amplicon size. The results indicated that diagnosis of Peste des petits ruminanats can be perform from necropsy material using molecular technique like PCR, which showed promising results.